CRISPR/Cas9-mediated editing of barley lipoxygenase genes promotes grain fatty acid accumulation and storability - Zhanghui Zeng; Huiling Wang; Yingjie Luo; Wenjun Chen; Mingrui Xu; Haonan Wei; Zhehao Chen; Taihe Xiang; Lilin Wang; Ning Han; Xiaoping Huang; Hongwu Bian (GM Crops & Food, 2025)
Plant lipoxygenases (LOXs) catalyze the oxidation of polyunsaturated fatty acids, which can adversely affect grain storability. Although the genetic engineering of LOXs holds great potential for improving grain storage quality, this approach remains largely unexplored in barley. In this study, we identified five LOX genes in the barley genome: HvLOXA, HvLOXB, and HvLOXC1–3. HvLOXC1 exhibited the highest expression in early developing grains, roots, and shoots; HvLOXA was predominantly expressed in embryos, whereas HvLOXB and HvLOXC3 were weakly expressed across tissues. Transgene-free homozygous barley mutants of loxB, loxC1, and loxAloxC1 were generated using CRISPR/Cas9-mediated genome editing. Compared to the wild-type, all mutants displayed normal plant height, tiller number, and grain size, although the loxC1 and loxAloxC1 mutants exhibited significantly lower thousand grain weights. Notably, the total LOX activity in mature grains decreased by 36–42% in loxC1 mutants and by 94% in loxAloxC1 mutants, with no significant change observed in loxB mutants. Additionally, the loxAloxC1 double mutants had a significantly lower malondialdehyde content and accumulated 10–21% more fatty acids than the wild-type. Artificial aging treatment experiments revealed that loxAloxC1 mutants had enhanced grain storability, demonstrated by significantly higher germination rates, reduced lipid peroxidation, and improved seedling growth. Our findings highlight that the targeted knockout of LOX genes, particularly the double mutation of HvLOXA and HvLOXC1, represents a promising genetic strategy for improving grain storability and nutritional value in barley.